Implementation of a prototype ADSL system using TI TMS320C6X DSP. - Manlapat, Alvin A. (Philippine engineering journal)
The Asymmetric Digital Subscriber Line (ADSL) is a local loop transmission technology that simultaneously transports downstream (towards customer) bit rates of up to 8 Mbps, and upstream (towards network) bit rates of up to 800 kbps, and plain old telephone service (POTS) via a single pair of wires. The increased bandwidth available allows real time applications like video on demand (VOD) live video conferencing and remote Local Area Network (LAN) access to be accessible via the public switched telephone network. This paper discusses the implementation of a prototype ADSL system on the Texas Instruments TMS320C6701 Digital Signal Processor Evaluation Module. The software blocks were coded and optimized in ANSI C and downloaded into the target system. A simplified frequency scaled model of the subscriber loop is used as the channel in testing the system in loop back mode. An online bit error rate test sequence was performed to determine system performance. An aggregate bit rate of 66.15 kbps with a bit error rate (BER) of approximately 10 to the seventh power was achieved.